3D kinematics in freestyle cross-country skiing (XCS) technigue during World Cup races (2012-13) - Canclini, A.; Canclini, A.; Baroni, G.; Pozzo, R. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aim of this work was to collect and to analyze the 3D kinematics of the typical strides in freestyle XCS performed by slite skiers engaged in recent World Cup races.